Utsman bin Mazh'un in Visual, Literature and International Exhibition - Lutfianto, Lutfianto; Munip, Abdul; Maharsi, Maharsi (Perhimpunan Intelektual Muslim Indonesia, 2025)
This paper aims to discuss Uthman bin Mazh'un's paragraph in visuals, literature in the Nusantara and the international exhibition of the power of the Ka'bah II. The character of the Prophet Muhammad's companion is that of a friend who cares about others' suffering. Next, the visual form of paraga Uthman bin Mazh'un will be explained, along with its meaning in a review of Indonesian literature and in the international exhibition of the power of the Ka'bah II. Visual, literary, and exhibition discussions will help readers understand the character in a cultural context. Visual paraga in the form of wayang implies a specific message to the audience. Especially when exhibited on the international scene. Apart from that, the messages in Javanese literature are moralistic and intended for connoisseurs. Therefore, Uthman bin Mazh'un's paragraph in the wayang Kekayon Khalifah can serve as a beautiful educational tool for the public, both in appearance and language.